TANTANGAN DAN TRANSFORMASI LAR DI KABUPATEN SUMBAWA: CATATAN AWAL TENTANG KETERBATASAN PENGEMBANGAN PULAU KECIL - Erwin Fahmi (PROSIDING SERINA, 2021)
Studies on the role of local institutions for the sustainability of regional development have been tremendous in the last 3-4 decades. Nobel laureate in Economics, E. Ostrom (1990), for instance, has shown how community-based voluntary institutions prove robust and long-enduring to support the sustainability of common-pool resources management.This study takes a step forward to investigate the challenges and transformation of such locallycreated institutions and their impacts on the sustainability of the development they are supporting. In the last 2 decades or so communal grazing areas in the District of Sumbawa have been facing various challenges which strongly affect their effectiveness or existence as stock feeder. Responding to such challenge large-scale stock farmers tend to solve those challenges by transforming into privately- owned grazing areas. Furthermore, findings of the study will also be used to further illustrate the issues of limited small island capacity development. This implies among other things that intensive animal husbandry development which may seems justifiable by innovation in animal husbandry technology cannot go beyond those limited capacity challenges, and the need to correct efforts contrary to this development direction, such as the corn extensive agricultural program.